15. CURRENT STATUS OF HUMAN LIVER FLUKE INFECTIONS IN THANH HOA AND NGHE AN PROVINCES IN THE PERIOD 2020-2022 (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe the prevalence of human live fluke infections in Thanh Hoa and Nghe An provinces in the period of 2020-2022.Research object: People in 2 communes Phu Lam, Tan Truong (Nghi Son town, Thanh Hoa province) and 2 communes Nghia Thuan, Nghia My (Thai Hoa town, Nghe An province).Method: Cross-sectional descriptive study, stool microscopy and serum Ab-ELISA.Results: The prevalence of human live fluke infections through fecal microscopy was 0.2%. The proportion of people with antibodies against human live flukes was 1.7%, including 1.6% in Phu Lam commune, 0.8% in Tan Truong commune, 2.6% in Nghia Thuan,  and 2.0% in Nghia Hung. The prevalence in the age group < 60 was 1.9%, and in the age group ≥ 60 was 0.9%. Female patients outnumbered male patients (2.0% and 1.4%).
Keywords: Human liver fluke; related factors; Thanh Hoa; Nghe An